Fraud prevention awareness and how it can create a competitive edge for bKash Limited in the mobile finance service industry - Kabir, Shadman Sakibul (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.